Evaluation of Drug Storage in the Pharmacy Installation Warehouse at RSUD dr. H. Moch. Ansari Saleh Banjarmasin - Nadia Nadia; Muhammad Zaini; Muliyani Muliyani (UPPM Politeknik Unggulan Kalimantan, 2024)
Drug management in the pharmacy warehouse has been regulated in pharmaceutical service standards in hospitals. Implementation of the standards set by the government needs to be seen and assessed to get a good picture of drug storage to ensure the quality of drugs in hospitals before distribution. The aim of this research is to determine the suitability of the method of storing medicines in the pharmacy installation warehouse at RSUD dr. H. Moch. Ansari Saleh Banjarmasin. This research is quantitative descriptive by making direct observations on the running system accompanied by observation, using a check list sheet and using a sampling method, namely the total sampling method, namely all drug preparations in the Pharmacy Installation Warehouse at RSUD dr. Moch. Ansari Saleh Banjarmasin 103 items of medicine. The research results show that drug storage in the pharmacy installation warehouse at RSUD dr. H. Moch. Ansari Saleh Banjarmasin is in the very good category (94%) according to. By obtaining suitability for dosage type (99%), drug stability (100%), alphabetical (77%), LASA (95%) and FEFO (97%).